Estudos interdisciplinares em torno de um códice iluminado do século XVIII - Rodolpho Antonio Pereira Zanibone (2024)
This dissertation examines the Livro de Compromisso da Irmandade da Igreja Matriz de Nossa Senhora do Bom Sucesso de Vila Nova da Rainha do Caeté, currently under the custody of the Arquivo Público Mineiro in Belo Horizonte, Minas Gerais. The Commitment Books of the Brotherhood, statutes that regulated brotherhoods in colonial society, transcend their juridical-administrative function, carrying symbolic and aesthetic values. The goal of the research, in a theoretical-practical context, is to conserve and restore this manuscript adorned by the 'Calligrapher of Golden Birds,' dated 1738, reflecting an Orientalized influence. Through the analysis of the subsequent insertion of elements into the structure of the codex, the research expands to understand its codicological, techniques, and materials, as well as degradations. In addition to identifying and characterizing the object, the research discusses significant damage caused by bibliophagous insects and stains resulting from moisture and microorganisms. A methodology for quantifying areas of support loss is presented, along with reflections on the challenges encountered in these aspects for its restoration. For this, the adopted methodology includes an interdisciplinary approach, incorporating physicochemical analyses as a fundamental part of the investigative process, applied to examine the composition of the materials used in the object's creation. The comparison of the results of these analyses between different parts of the manuscript (frontispiece, engraving, and main body) validates the hypothesis of the later insertion of the frontispiece and the engraving, suggesting a folio produced by the same “Calligrapher of the Golden Birds”, which would have been adapted to integrate the manuscript. Furthermore, the identification of materials distinct from its palette in the engraving indicates the participation of another artisan in localized areas of its ornamentation.